Folded planar resonator-based sonic Crystal scatterer: Part I. Shifting from split tube resonator design. Issue 1 (April 2021) - Yahya, Iwan; Suparmi,; Cari,; Ubaidillah,
Abstract: A split tube resonator (STR) is one of the typical base structures in many previous acoustic metamaterial structures. This paper introduces a brand new approach to designing the tunable concentric wall resonating structure to look like a similar shape but with a different response and performance to STR. The central concept is a planar resonator folded outward and inward direction. We found that the proposing approach gives the possibility for a single geometrical dimension tunable sonic crystal element that could not occur in a single degree of freedom conventional STR. The test model made of stiff paper and the sound absorption performance test conducted experimentally with impedance tube refers to ASTM E-150-98 standard.